Política de discapacidad e inclusión at Universidad del Valle: A Participatory Process - Carvajal Osorio, Mónica María (Sociedad y Economía, 2015)
The population with disabilities is one of the groups at social risk of exclusion within different citizen’s life settings including higher education. Universidad del Valle, in the process of recognizing the disability, undertook the construction of Política de discapacidad e inclusión with the participation of diverse actors from the University community. Through the analysis of documentary sources, this systematization describes three main characteristics of the process: participative character and joint responsibility of actors, formative approach and networking. Results of this study will contribute to guide the design of other disability policies and constitutes a valuable experience focusing on the construction of community identity for institutional development: “recognition” of disability and persons with disability.